(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to determine the total cost of travel tickets for airline companies and the extent of the impact of using the positioning strategy in determining costs in addition to the pricing of flight tickets in light of the positioning strategy. The research attempts to develop solutions to the problems of high costs of flight tickets in the General Company of Iraqi Airlines, due to the lack of adoption of techniques Modern cost-effectiveness in pricing, which led to the company not being competitive with other companies, as determining the costs of tickets for flights raised the level of competitiveness of the company and monitored its performance. The research led to a set of results, the most important of which are: The management does not rely on specific strategies based on scientific foundations in constructing the cost of tickets for various flights and pricing them. Analyzing the cost, determining it, reducing it, and arriving at flexible prices is considered the best option for the company in achieving competitiveness and market positioning among air transport companies while ensuring the quality of service for passengers. It is considered to adopt a positioning strategy. The market enables departments to re-examine and analyze prices in the market to formulate opportunities to reduce costs and introduce new, flexible prices for air transport services, which may increase the company’s market share.